Step * 1 1 1 1 1 of Lemma sinh-inv-sinh


1. : ℝ
2. (r0 ≤ ((x x) r1)) ∧ (r0 < (x rsqrt((x x) r1)))
3. : ℝ
4. rlog(x rsqrt((x x) r1))
5. ln(x rsqrt((x x) r1)) v ∈ {x1:ℝx1 rlog(x rsqrt((x x) r1))} 
6. v1 : ℝ
7. v1 e^v
8. expr(v) v1 ∈ {y:ℝe^v} 
9. v2 : ℝ
10. v2 e^-(v)
11. expr(-(v)) v2 ∈ {y:ℝe^-(v)} 
12. v1 (x rsqrt((x x) r1))
13. v2 (r1/v1)
⊢ (v1 -((r1/v1))) (r(2) x)
BY
(nRMul ⌜v1⌝ 0⋅ THENA Auto) }

1
1. : ℝ
2. (r0 ≤ ((x x) r1)) ∧ (r0 < (x rsqrt((x x) r1)))
3. : ℝ
4. rlog(x rsqrt((x x) r1))
5. ln(x rsqrt((x x) r1)) v ∈ {x1:ℝx1 rlog(x rsqrt((x x) r1))} 
6. v1 : ℝ
7. v1 e^v
8. expr(v) v1 ∈ {y:ℝe^v} 
9. v2 : ℝ
10. v2 e^-(v)
11. expr(-(v)) v2 ∈ {y:ℝe^-(v)} 
12. v1 (x rsqrt((x x) r1))
13. v2 (r1/v1)
⊢ (r(-1) (v1 v1)) (r(2) v1 x)


Latex:


Latex:

1.  x  :  \mBbbR{}
2.  (r0  \mleq{}  ((x  *  x)  +  r1))  \mwedge{}  (r0  <  (x  +  rsqrt((x  *  x)  +  r1)))
3.  v  :  \mBbbR{}
4.  v  =  rlog(x  +  rsqrt((x  *  x)  +  r1))
5.  ln(x  +  rsqrt((x  *  x)  +  r1))  =  v
6.  v1  :  \mBbbR{}
7.  v1  =  e\^{}v
8.  expr(v)  =  v1
9.  v2  :  \mBbbR{}
10.  v2  =  e\^{}-(v)
11.  expr(-(v))  =  v2
12.  v1  =  (x  +  rsqrt((x  *  x)  +  r1))
13.  v2  =  (r1/v1)
\mvdash{}  (v1  +  -((r1/v1)))  =  (r(2)  *  x)


By


Latex:
(nRMul  \mkleeneopen{}v1\mkleeneclose{}  0\mcdot{}  THENA  Auto)




Home Index